Variants near CHRNA3/5 and APOE have age- and sex-related effects on human lifespan - Peter K. Joshi (Nature Portfolio, 2016)
Understanding the genetic influences on human aging requires a large number of subjects for a study of sufficient power. Here, Jim Wilson and colleagues use information on parental ages at death to show that common variants near the genes for apolipoprotein E and nicotinic acetylcholine receptor subunit alpha 5 are associated with longer lifespan.